Pengaruh Digitalisasi, Literasi Keuangan, dan Dukungan Teknologi terhadap Kinerja Keuangan UMKM di Kabupaten Karanganyar - Lady Noor; Mirzam Arqy Ahmadi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Amidst the challenges of technology adoption, Indonesian MSMEs have a great opportunity to improve efficiency, competitiveness, and sustainability through digitalization. With a large contribution to GDP and employment, MSMEs need to utilize fiscal incentives, digital strategies, and online payment methods to meet the needs of modern customers. This transformation not only helps businesses operate, but also opens up opportunities for growth in the age of technology. This study looks at how digitalization, financial literacy, and technology support affect the financial performance of MSMEs. It also looks at how these factors affect productivity, efficiency and day-to-day operations in the digital age. This study aims to evaluate the impact of these three components on the financial performance of MSMEs in Karanganyar Regency. This study uses primary data from questionnaires given to MSME owners. The study findings show that financial literacy, financial inclusion, and technology use significantly improve the financial efficiency of MSMEs by helping with financial management, capital access, and business sustainability. However, the limitation of this study is the limited scope that only covers a part of the sample of MSMEs in Karanganyar Regency, so it cannot represent all MSMEs more broadly.